GAS6/TAM signaling pathway controls MICA expression in multiple myeloma cells - Kosta, Andrea; Mekhloufi, Abdelilah; Lucantonio, Lorenzo; Zingoni, Alessandra; Soriani, Alessandra; Cippitelli, Marco; Gismondi, Angela; Fazio, Francesca; Petrucci, Maria Teresa; Santoni, Angela; Stabile, Helena; Fionda, Cinzia (Frontiers in Immunology, 2022)
NKG2D ligands play a relevant role in Natural Killer (NK) cell -mediated immune surveillance of multiple myeloma (MM). Different levels of regulation control the expression of these molecules at cell surface. A number of oncogenic proteins and miRNAs act as negative regulators of NKG2D ligand transcription and translation, but the molecular mechanisms sustaining their basal expression in MM cells remain poorly understood. Here, we evaluated the role of the growth arrest specific 6 (GAS6)/TAM signaling pathway in the regulation of NKG2D ligand expression and MM recognition by NK cells. Our data showed that GAS6 as well as MERTK and AXL depletion in MM cells results in MICA downregulation and inhibition of NKG2D-mediated NK cell degranulation. Noteworthy, GAS6 derived from bone marrow stromal cells (BMSCs) also increases MICA expression at both protein and mRNA level in human MM cell lines and in primary malignant plasma cells. NF-kB activation is required for these regulatory mechanisms since deletion of a site responsive for this transcription factor compromises the induction of mica promoter by BMSCs. Accordingly, knockdown of GAS6 reduces the capability of BMSCs to activate NF-kB pathway as well as to enhance MICA expression in MM cells. Taken together, these results shed light on molecular mechanims underlying NKG2D ligand regulation and identify GAS6 protein as a novel autocrine and paracrine regulator of basal expression of MICA in human MM cells.